Design and implementation of smart electronic solar tracker based on Arduino - Muthna Jasim Fadhil; Rashid Ali Fayadh; Mousa K. Wali (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Demand of energy increases in the global and exponential exhaustion is favored of resources by fossil fuel for electricity production with the new systems development. Compared with all other remainder energies, the specialist sun energy is the most bountiful energy and it's typically easy to be changed into electrical energy. The main thing of using solar panel is to produce electrical energy from sun's energy but the optimum energy can be generated by tracking solar panel due to the sun movement from east to west. The problem can be solved by proposed systems where the sun tracking by solar panel that based on high intensity of sun ray.  This paper concentrates on tracking the sun by using servo motor coupled with solar panel. So that, the largest quantity of sun light at the incident panel along the day at any time is better than that for method of fixed panel array which is less efficient. The microcontroller Arduino (mode UNO) was programmed by using C++ language while the track of sun light processing was implemented by using light depending resistor (LDR), Chip IC H-bridge and microcontroller Arduino (UNO) circuits have been designed by using Proteus software. By circuit design and sun tracking control process, the cost reduction has been improved and high amount of energy was saved when implemented this system.